SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SISWA BERPRESTASI SEBAGAI PESERTA OLIMPIADE SAINS MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Haryo Kusumo (UNIVERSITAS STEKOM, 2020)
Abstract The development of science in the era of information technology today indirectly also has an impact on the world of education, especially in the selection of students as participants in the Science Olympics. MTs X need a decision support system that can classify the selection pattern of junior high school science Olympiad students by considering several criteria, namely test results, subject values, Olympic experience, report card grades, and grade level. The model used in this decision support system is Fuzzy Multiple Attribute Decision Making, using the Simple Additive Weighting method, because this method determines the weight value for each attribute, then continues with the ranking process that will select the best alternative from a number of alternatively, in this case the alternative in question is an outstanding student who will be a Science Olympiad participant. The result is that the determination of Science Olympiad participants is more accurate.